Perbandingan antara Pendapatan Rumah Tangga Petani di Subak Daerah Pariwisata dan Non Pariwisata - MELITA ISTI SEPTIASARI; I KETUT SURYA DIARTA; RATNA KOMALA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2013)
ABSTRACT Comparison between Farmers Household Income in The Subak of Tourism and Non Tourism Area Household income of farmers in the area of subak in tourism and non tourism is different. Diversity of household income of farmers in Subak tourism and non-tourism areas makes it worthy to be known in order to see the effect of tourism on agriculture, especially subak development. The research objective is to determine the ratio of household income from agriculture and non-agricultural sectors in the subak of tourism and non tourism area. Total income of farm households in the subak areas of tourism and non-tourism income derived from agriculture and non-farm sector income. Income households in the tourist areas of the agricultural sector amounted to 14.39% while the non-agricultural sector amounted to 85.61%. The households’ income in non-tourism areas of the agricultural sector amounted to 35.64%. Research shows total income of farm households in the area of ??tourism and non-tourism is different. It can be seen from the t- test with a significance value of 0.000 with a t-value of 4.003. Subak farmers in the tourism area are expected to set aside revenue from non agricultural sector to increase income from non-agricultural sector, farmers in the non tourism a part from relying on the main livelihood from agriculture they also rely on non-agricultural sector as side income so that livelihoods of farmers' household income increased, members farming households are expected to remain as in average farmers have started entering unproductive age so the need for regeneration is highly required. Keywords: household income, In the Subak of Tourism and Non Tourism Area